1989
DOI: 10.1097/00000658-198901000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Parotid Fistulae and Sialoceles. A Prospective Study of Conservative Management in 51 Cases

Abstract: The management of parotid sialoceles and fistulae have been unsatisfactory in the past, and numerous methods of treatment with varying success and morbidity have been described. The present prospective study reports results of conservative therapy in 51 patients over a 3-year period. In 50 patients, the injury healed upon conservative management. During the early phase of the study, a limited conservative regimen through which the patients received nothing orally for 5 days only was used. During the latter par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
96
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 21 publications
0
96
0
4
Order By: Relevance
“…Antisialogogue medications including anticholinergic agents are also administered to inhibit the action of acetylcholine at the postganglionic nerve endings of the parasympathetic nervous system. However, side effects can included xerostomy, constipation, photophobia, tachycardia, and urinary retention [5]. When conventional conservative management fails, BTX is considered.…”
Section: Discussionmentioning
confidence: 99%
“…Antisialogogue medications including anticholinergic agents are also administered to inhibit the action of acetylcholine at the postganglionic nerve endings of the parasympathetic nervous system. However, side effects can included xerostomy, constipation, photophobia, tachycardia, and urinary retention [5]. When conventional conservative management fails, BTX is considered.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies have reported that correction of these complications may require surgical or medical treatments like use of anti sialogogues, radiation therapy, parasympathetic denervation (tympanic denervation), cauterization of the fistulous tract and reconstruction of the duct, superficial or total parotidectomy. 3,8 A significant delay in the healing of complications was noted when there was total transaction of duct. 9 Immediate microsurgical anastomosis of the parotid duct injury is one such modality of treatment, which will possibly prevent such complications.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management has been recommended [4,5] as the treatment of choice for post traumatic fi stula. It is when fi stula does not respond by these measures that further active intervention is required.…”
Section: Discussionmentioning
confidence: 99%